2014
DOI: 10.1038/tp.2013.123
|View full text |Cite
|
Sign up to set email alerts
|

Increased binding of MeCP2 to the GAD1 and RELN promoters may be mediated by an enrichment of 5-hmC in autism spectrum disorder (ASD) cerebellum

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by symptoms related to altered social interactions/communication and restricted and repetitive behaviors. In addition to genetic risk, epigenetic mechanisms (which include DNA methylation/demethylation) are thought to be important in the etiopathogenesis of ASD. We studied epigenetic mechanisms underlying the transcriptional regulation of candidate genes in cerebella of ASD patients, including the binding of MeCP2 (methyl CpG binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
99
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 37 publications
15
99
1
Order By: Relevance
“…54,57 Our MeDIP-Seq data from human brain reveal the mutual exclusivity of these DNA modifications and provides additional support for a role of 5hmC distinct from that of 5mC, including a previously unappreciated potential role at the TES of genes. Future studies that utilize 5hmC MeDIP-Seq as a cost-effective and rapid technique to assess differences between the brain from normal and disease conditions, such as Autism Spectrum Disorder, 61 Alzheimer disease, 62 or Schizophrenia, 63 may lead to further insight into the functional importance of 5hmC. Given the appropriate antibodies, this Ion Torrent MeDIP-Seq approach potentially offers a means to study the functional importance of other poorly understood DNA modification variants such as 5-formylcytosine and 5-carboxycytosine.…”
Section: Discussionmentioning
confidence: 99%
“…54,57 Our MeDIP-Seq data from human brain reveal the mutual exclusivity of these DNA modifications and provides additional support for a role of 5hmC distinct from that of 5mC, including a previously unappreciated potential role at the TES of genes. Future studies that utilize 5hmC MeDIP-Seq as a cost-effective and rapid technique to assess differences between the brain from normal and disease conditions, such as Autism Spectrum Disorder, 61 Alzheimer disease, 62 or Schizophrenia, 63 may lead to further insight into the functional importance of 5hmC. Given the appropriate antibodies, this Ion Torrent MeDIP-Seq approach potentially offers a means to study the functional importance of other poorly understood DNA modification variants such as 5-formylcytosine and 5-carboxycytosine.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of Alzheimer's disease there is increasing evidence that changes of 5hmC play a crucial role for the progression of the disease (Bradley-Whitman and Lovell 2013;Condliffe et al 2014;van den Hove et al 2012). But also in the context of mental disorders, recent studies imply that 5hmC is closely associated with autism (James et al 2014;Zhubi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies challenge this finding by showing no significant reduction in GABRB3 mRNA and protein levels in brain tissues of MeCP2-deficient mice [114,115]. LaSalle reasons the time point of MeCP2-deficient mice used or RT-PCR issues to explain the discrepancies observed in these later studies [105,106,116]. Some studies have linked the decreased GABRB3 expression in MeCP2 deficiency with decreased expression of the ubiquitin protein ligase E3A (UBE3A) gene [109,112,113].…”
Section: Mecp2 - Additional Regulations In Gabaergic Neurotransmissionmentioning
confidence: 38%
“…One of the above studies that looked at cytoplasmic adaptor protein Disabled-1 (Dab1) KO mice showed no reelin-mediated phosphorylation and calcium influx demonstrating that phosphorylation of NMDAR receptor is a key step of the mechanism; Dab1 acts downstream of reelin to mediate the phosphorylation [98]. Another important player in the DNMT-regulated hypermethylation is MeCP2, an epigenetic reader, which shows increased affinity to methylated CpG in GAD67 and RELN gene promoters and acts as a transcriptional repressor [104,105,106]. MeCP2 and HDAC are the components of the repressor complex formed in the DNMT1-methylated site, which is seen in SZ patients or SZ mice models [107].…”
Section: Dna Methylation - Dnmt1 and Mecp2-mediated Transcriptional Smentioning
confidence: 99%